EXPLANATION OF THE FREQUENCY-VOLUME DEPENDENCE FOR VOLCANIC ERUPTIONS - Golitsyn G.S. (My University, 2003)
The global-scale empirical dependence between cumulative frequency and size of volcanic eruptions (VEs) [1] is explained in this work. This frequency is proportional to the volume of erupted ash to a power of 0.7. It is shown that this regularity is similar to the Guttenberg-Richter law for earthquake recurrence. It is estimated that a few tenths of percent of the Earth's total geothermal flux is spent to maintain volcanic activity.